Overexpression of the truncated form of high mobility group a proteins (HMGA2) in human myometrial cells induces leiomyoma-like tissue formation - Mas, Aymara (2014)
The pathogenesis of uterine leiomyomas, the most common benign tumor in women, is still unknown. This lack of basic knowledge limits the development of novel non-invasive therapies. Our group has previously demonstrated that leiomyoma side population (SP) cells are present in tumor lesions and act like putative tumor-initiating stemcells in human leiomyoma. Moreover, accumulated evidence demonstrates that these benign tumors of mesenchymal origin are characterized by rearrangements of the High Mobility Group A proteins (HMGA). In this work, we tested the hypothesis that leiomyoma development may be due to overexpression of HMGA2 (encoding high mobility group AT-hook2) in myometrial stem cells using in vitro and in vivo approaches. Our work demonstrates that the truncated/short form of HMGA2 induces myometrial cell transformation toward putative tumor-initiating leiomyoma cells and opens up new possibilities to understand the origin of leiomyomas and the development of new therapeutic approaches.